PELATIHAN PENGGUNAAN SISTEM OJS BAGI PENDIDIK DI SMP N 1 KEFAMENANU - Faizal Arvianto; Giri Indra Kharisma (Politeknik Negeri Sriwijaya, 2021)
Based on interviews with head master of SMP N 1 Kefamenanu, data was obtained only 2% out of 20 teachers understood the OJS system who received promotions with the condition that they did scientific publications in national journals. Based on these problems, the authors conducted training them to use OJS system to increase the capacity of scientific publications at SMP N 1 Kefamenanu. This activity use participatory action research (PAR) as a method which use three stages, namely preparation, implementation and evaluation. The responses from the participating teachers indicated that this training activity was very useful. Teachers of SMP N 1 Kefamenanu now understand and understand how to submit articles using the OJS system. In addition, 1 out of 16 assisted subjects have succeeded in getting a response that their articles were received with corrections by the journal editor as a form of success in training activities.